Efficient market hypothesis in European stock markets - Borges, Maria Rosa (2022)
This paper reports the results of tests on the weak-form market efficiency applied to stock market indexes of UK, France, Germany, Spain, Greece and Portugal, from January 1993 to December 2007. We use a runs test, and joint variance ratio tests, which are performed using daily and weekly data for the period 1993–2007 and for a subset, 2003–2007. Daily and weekly returns are not normally distributed, because they are negatively skewed and leptokurtic, and also display conditional heteroscedasticity. Overall, we find mixed evidence on the efficient market hypothesis (EMH). The hypothesis is rejected on daily data for Portugal and Greece, due to first-order positive autocorrelation in the returns. However, the empirical tests show that these two countries have been approaching a martingale behavior after 2003. France and UK data rejects EMH, due to the presence of mean reversion in weekly data, and stronger in recent years. Taken together, the tests for Germany and Spain do not allow the rejection of EMH, this last market being the most efficient.